(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
For a class of Lotka-Volterra competitive systems including both diffusion and advection, a global bifurcation result of positive steady states is established via a bifurcation approach. Also, the phenomenon of multiple positive steady states is discussed.